Features of creating an optimal microclimate in the poultry room - Skliar, Oleksandr; Скляр, Олександр Григорович; Skliar, Radmila; Скляр, Радміла Вікторівна; Boltianskyi, Borys; Болтянський, Борис Володимирович (Stockholm, Sweden, 2023)
EN: Due to unsatisfactory zoohygienic conditions, the potential productivity of poultry is often used only by 20...30%, their life span is shortened. Therefore, the creation of an optimal microclimate in industrial poultry farming is the most important reserve for increasing the production of high-quality products [1]. In addition, it is important for extending the service life of buildings and technological equipment, as well as for improving the working conditions of service personnel.
Особливості створення оптимального мікроклімату в пташнику